Segregando para “cuidar”: política de Estado para controle da lepra - 1950/1960 - Silva, Nayara Alexandra Rodrigues da (2019)
This study has as its object the policy of confronting Leprosy by the State in the 1950s / 60s, as part of the control of the endemic diseases of underdeveloped countries. This is a historical study from the Postgraduate Program in Nursing of the Federal University of Alagoas. The same is still tied to the Study Group D. Isabel Macintyre, of which the researcher and counselor are members. The research was promoted by the Conselho Nacional de Desenvolvimento Científico e Tecnológico - CNPQ e da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – CAPES. Its objectives were: To describe the actions of the government in the control of Leprosy in the decades of 1950/1960; Analyze the measures adopted in Alagoas to fulfill the public policy instituted and discuss the symbolic power of the state manifested in the segregation of the lepers to another state with reflexes in their lives. For this purpose we have resorted to Pierre Bourdieu's thinking and his conceptions about State, state control and symbolic violence. The data were obtained through interviews with the interlocutors, analysis of newspaper clippings of the time and the manuals, bulletins, decrees and Brazilian laws alluding to the cut and object of the study. In spite of treating the disease as leprosy, its scientific name is recognized today, in the texts of the policies of the time and in connection with the disease the term "Leprosy", denomination also comes from biblical texts, that contributed to perpetuate the stigma in around 1973, the Brazilian State created a legal framework to change the way the disease is treated socially. It was chosen as an example of execution of the State policy to actions of the government of Alagoas, where in the temporal cut described, experienced in an intensified way the actions to combat the disease, expressed by the compulsory removal of patients with the disease to the state of Pernambuco, after the closing of the only Alagoas Colony Hospital. The approach to the sources allowed the researcher to understand and reflect on how the reproduction of the official discourse of the State along with the prejudices rooted in the Brazilian society creates a context of segregation and disengagement to the patients of the disease, affecting their processes of identity construction, formation of their ties and expression of their affections.